2018
DOI: 10.1186/s13293-018-0209-3
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in distribution of cannabinoid receptors (CB1 and CB2), S100A6 and CacyBP/SIP in human ageing hearts

Abstract: BackgroundWomen live about 4 years longer due to lower prevalence of cardiovascular complication with ageing. However, the mechanisms involved in the preservation of heart functionality in women have not been fully elucidated.The endocannabinoid system fulfils a significant role in the regulation of cardiovascular system functioning. Cannabinoids, acting through specific receptors (CB1 and CB2), influence on blood pressure, heart rate and myocardial contractility. The function of cardiac muscle cells is strict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 41 publications
0
20
2
Order By: Relevance
“…Increased female expression of ABHD6 has been previously reported in immune cells, with only female cells showing estrogen- or progesterone-dependent induction of ABHD6 gene levels. Our observations of minor sex-dependent effects on the expression of the 27-gene endocannabinoid signature contrast with sex differences in the expression of CB 1 and CB 2 protein expression in heart tissue, where CB 1 receptors are more highly expressed in females and CB 2 receptors more highly expressed in males(94). Our observations of limited impact of sex on the 27-gene endocannabinoid signature expression in healthy subjects were conserved in asthmatics and individuals with COPD.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Increased female expression of ABHD6 has been previously reported in immune cells, with only female cells showing estrogen- or progesterone-dependent induction of ABHD6 gene levels. Our observations of minor sex-dependent effects on the expression of the 27-gene endocannabinoid signature contrast with sex differences in the expression of CB 1 and CB 2 protein expression in heart tissue, where CB 1 receptors are more highly expressed in females and CB 2 receptors more highly expressed in males(94). Our observations of limited impact of sex on the 27-gene endocannabinoid signature expression in healthy subjects were conserved in asthmatics and individuals with COPD.…”
Section: Discussioncontrasting
confidence: 77%
“…Sex differences in CB 1 and CB 2 expression levels have been reported(94), which could impact downstream responses to cannabinoid exposures. Furthermore, sex and gender differences in cannabis consumption practices have been reported(2-4).…”
Section: Resultsmentioning
confidence: 99%
“…Sex differences in CB 1 and CB 2 expression levels have been reported [ 98 ], which could impact downstream responses to cannabinoid exposures. Furthermore, sex and gender differences in cannabis consumption practices have been reported [ 2 – 4 ].…”
Section: Resultsmentioning
confidence: 99%
“…The activation of the CB1R in isolated rat atria results in feeble cardiomyocyte contractility [59]. Numerous in vivo studies have demonstrated that activation of CB1R promotes cardiomyocyte injury, oxidative stress, inflammation, and fibrosis, and augments collagen deposition and cardiomyocyte overgrowth [60,61,62]. Thus, chronic inhibition of CB1R with rimonabant improves cardiac functions in the early and late stages after myocardial infarction, decreases arterial stiffness, and reduces cardiac remodeling [63,64].…”
Section: Distribution and Biological Roles Of Cb1r In The Human Bodymentioning
confidence: 99%